CCNA : Cisco Certified Network Associate study guide - Lammle, Todd (Serious skills., 2011)
"The leading CCNA certification guide, fully updated for the newest version of the exam The Cisco Certified Network Associate certification is the first step for network administrators seeking to advance their careers. Written by networking authority Todd Lammle, this comprehensive, fully updated study guide covers everything you need to know to pass the exam. It examines every exam objective, provides expanded coverage of key topics, and includes a CD with valuable video and audio files, the Sybex Test Engine, flashcards, and the entire book in searchable PDF format. Network professionals who hold the Cisco Certified Network Associate certification generally earn more than coworkers who have not earned the CCNA This comprehensive guide by author and trainer Todd Lammle provides everything you need to know about the areas covered on the latest version of the CCNA exam: network planning and design, implementation and operation, troubleshooting, and technology Includes a CD with more than an hour of valuable audio and video files, the Sybex Test Engine, flashcards, and the entire book in searchable PDF format CCNA candidates will find that CCNA: Cisco Certified Network Associate Study Guide, 7th Edition greatly improves their chances for success."--